Improvements to the Environmental Performance of Synthetic-Based Drilling Muds - Bakhtyar, Sajida; Gagnon, Marthe Monique (Wiley-VCH Verlag & Co., 2012)
Drilling muds used by the petroleum exploration and production industry have the role of lubricating and cooling the drilling bits and facilitating the transport of crushed rocks to the surface of the well. The chemical formulations of the drilling muds influence their fate when discharged into the marine environment and, along with ambient parameters, determine the biodegradability and toxicity of the muds. A case study describes the comparison of aquatic toxicity and biodegradability of two different synthetic-based drilling mud systems (SBMs), Syndrill 80:20 and Syndrill 90:10, and also individual mud ingredients. Chronic fish toxicity was measured using a suite of biomarkers of fish health. Preliminary tests led to the selection of the drilling mud Syndrill 80:20, and toxicity testing of individual ingredients of this mud showed that the primary emulsifier was the most aggressive component among all the mud ingredients tested. The present study aimed at developing an ecologically safe, green SBM by further improvements to Syndrill 80:20 through replacement of the most aggressive emulsifier with an alternative low/non-toxic alternative.The existing Syndrill 80:20 formulation was re-engineered by the incorporation of two alternative emulsifiers as replacements for the existing aggressive emulsifier. The new modified Syndrill 80:20 was then evaluated for its chronic toxicity against the existing Syndrill 80:20 using a suite of biomarkers of fish health. Following exposure to the modified mud system, pink snapper (Pagrus auratus) demonstrated weaker biological reactions as measured by ethoxyresorufin-O-deethylase (EROD) activity, biliary metabolites, and serum sorbitol dehydrogenase (SDH) activity. Closed-bottle biodegradation tests also indicated that the new formulation is actively biodegrading under marine anaerobic conditions. Therefore, the information on the toxicity of the re-engineered SBM provides an initial basis for evaluating its environmental performance in marine ecosystems, and may assist regulatory authorities in gaining a better understanding of the fate of SBMs in the marine environment.